Porous biological carbon fiber foam combined by aluminum phosphate for enhancing electric heating and electric thermal storage performance. (30th November 2022) - Leng, Guoqin; Duan, Shengzhi; Liu, Xianjie; Lin, Fankai; Yang, Yifan; Min, Xin; Mi, Ruiyu; Wu, Xiaowen; Liu, Yangai; Fang, Minghao; Huang, Zhaohui
Abstract: Electric heating, as a kind of clean heating approach, has aroused worldwide interest due to its exceptional energy conservation, high efficiency, and random switching modulation. However, it is still a great challenge on the practical application of carbon-based electrothermal composites, since the degradation of material long-time operation performances caused by the agglomeration of carbon fillers and the aging of polymer substrates. Herein, we propose a novel porous carbon fiber foam connected by the inorganic compound aluminum phosphate (CKFC), based on the kapok fibers via a vacuum impregnation and carbonization process. The additive agent, including aluminum dihydrogen phosphate and iron(III) chloride hexahydrate, could help to maintain the hollow cylindrical structure, produce more micropores in the carbon fibers, and ensure the fibers are firmly bonded together. The hierarchical carbon fiber structure and strong interfacial interactions endow the CKFC composite with fast heating response speed, high balance temperature under low input voltages (below 36 V), uniform surface temperature distribution, and desirable service stability during the electric heating. Impressively, the further prepared CKFC/paraffin composite exhibits an ultrahigh heat storage efficiency (97.9 %), which could also quickly raise the temperature to 45 °C within safety voltage and delay the heat release. Therefore, we believe that the CKFC/paraffin composite with excellent electric heating and electric thermal storage performances could hold great promise for the practical application in electric indoor heating. Graphical abstract: SEM of carbonized kapok fibers before and after modification (left). Time-histories of input voltage, specimen temperature, electrical resistance, and input electric power of the modified sample (right). Unlabelled Image Highlights: A cylindrical fibers with many micropores inner the fibers are prepared. The sample has fast response time and good service stability. The sample can achieve high equilibrium temperature under safe voltage. The heat storage efficiency of the sample/PA up to 97.9 %